Conjugated Polymer/Photochromophore Binary Nanococktails: Bistable Photoswitching of Near-Infrared Fluorescence for In Vivo Imaging - Jeong, Keunsoo; Park, Solji; Lee, Yong-Deok; Lim, Chang-Keun; Kim, Jungahn; Chung, Bong Hyun; Kwon, Ick Chan; Park, Chong Rae; Kim, Sehoon (WILEY-V C H VERLAG GMBH, 2013)
Nanoscopic dense integration between solid-state emission and photochromism provides nanoprobes capable of photoswitching of bright NIR fluorescence with high on/off contrast, bistability and improved signal identification, being suitable for imaging applications in autofluorescence-rich in vivo environments.
Keywords: AGGREGATION-INDUCED EMISSION; ORGANIC NANOPARTICLES; PROBES; PHOTOCHROMISM; NANOMEDICINE; TUMORS; CELLS